Ethanol Disinhibits Dorsolateral Striatal Medium Spiny Neurons Through Activation of A Presynaptic Delta Opioid Receptor - Patton, Mary H (Neuropsychopharmacology, 2016)
The dorsolateral striatum mediates habit formation, which is expedited by exposure to alcohol. Across species, alcohol exposure disinhibits the DLS by dampening GABAergic transmission onto this structure's principal medium spiny projection neurons (MSNs), providing a potential mechanistic basis for habitual alcohol drinking. However, the molecular and circuit components underlying this disinhibition remain unknown. To examine this, we used a combination of whole-cell patch-clamp recordings and optogenetics to demonstrate that ethanol potently depresses both MSN- and fast-spiking interneuron (FSI)-MSN GABAergic synaptic transmission in the DLS. Concentrating on the powerfully inhibitory FSI-MSN synapse, we further show that acute exposure of ethanol (50 mM) to striatal slices activates delta opioid receptors that reside on FSI axon terminals and negatively couple to adenylyl cyclase to induce a long-term depression of GABA release onto both direct and indirect pathway MSNs. These findings elucidate a mechanism through which ethanol may globally disinhibit the DLS.